Environmental Correlates of Physical Activity in Mexican-American Children at Home - McKenzie, Thomas L. (2008)
BACKGROUND: Understanding home environments may shed light on factors contributing to reduced physical activity (PA) in children, particularly minorities. Few studies have used micro-level observations to simultaneously assess children’s PA and associated conditions in homes. METHODS: Trained observers assessed PA and associated physical and social environmental variables in the homes of 139 Mexican-American children (69 boys, 70 girls; mean age=6 years) after school. RESULTS: Children spent most time indoors (77%) and being sedentary (74%). Reduced PA was associated with viewing media, being indoors, and parents being present. Increased PA was associated with prompts for PA and other children being present. PA prompts differed by child gender and location and prompter age status. CONCLUSIONS: Children are frequently sedentary at home. Micro-level observations showed PA is associated with potentially modifiable social and physical factors, including spending time outdoors. Studies to determine whether interventions on these correlates can improve children’s PA are needed.